Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Dan Sikap Keluarga Dan Masyarakat Yang Terdapat Pasien Pasca Pasung Di Tawangsari - Aji, Hafit Prasetyo Bayu; , Arif Widodo, A.Kp., M.Kes (2016)
EFFECT OF HEALTH EDUCATION ON KNOWLEDGE AND ATTITUDE OF FAMILY AND COMMUNITY CONTAINED IN PATIENTS POST PASUNG TAWANGSARI Abstracts By: Hafit Prasetyo Bayu Aji Background: Pasung is one of adjudication method by heading movement of patient with mental illness. In 2014, Indonesia issued law number 18 chapter IX related deprivation. Before this regulation, family and community did pasung to prevent the patient to damage or harm others. Health education is a good way to educate families and communities regarding knowledge and attitudes to take care of patient with mental illness, therefore there is no pasung in the future. Purposes: The aim of this research is to determine the effect of health education on knowledge and attitudes in patient with post-pasung in Tawangsari District. Methods: the type of research was quantitative study with quasi experiment method. The research sampel were 37 samples. The reasearch instrument used questionnaire, health education used power point and leaflets. The result of normality test used Shapiro-Wilk test obtained normal distribution data, thus as to analyze data used paired sample t test. Results: there was a statistically significant difference between knowledge and attitudes before and after giving health promotion with sig. (2-tailed) 0.001. Conclusions: The results are consistent with Arinze-Onyia, et al (2010) research, entitled The Effects of Health Education on Knowledge and Attitudes to Emergency Contraception by Female Student of a Tertiary Educational Institution n Enugu, South East Nigeria stated that there is a significant increase of student knowledge and attitudes after doing health education with a value of p <0,05. Conclusion. The results of this study showed that health education with the lecture method , can effectively enhance the knowledge and attitudes of families and communities in Kedung Jambal. Keywords : Health Education, Knowledge, Attitudes, Mental Illness, Pasung